Improvement of coastal and mesoscale observation from space: Application to the northwestern Mediterranean Sea. Issue 10 (26th May 2013) - Escudier, Romain; Bouffard, Jérôme; Pascual, Ananda; Poulain, Pierre‐Marie; Pujol, Marie‐Isabelle
Abstract: [1] We present an innovative approach to the generation of remotely sensed high‐resolution sea surface topography that improves coastal and mesoscale dynamic characterization. This new method is applied for the period 2002–2010 in the northwestern Mediterranean Sea, an area marked by a small Rossby radius. The spectral content of the new mapped data is closer to that of the along‐track signal and displays higher levels of energy in the mesoscale bandwidth with the probability distribution of the new velocity fields 30% closer to drifter estimations. The fields yield levels of eddy kinetic energy 25% higher than standard altimetry products, especially over regions regularly impacted by mesoscale instabilities. Moreover, qualitative and quantitative comparisons with drifters, glider, and satellite sea surface temperature observations further confirm that the new altimetry product provides, in many cases, a better representation of mesoscale features (more than 25% improvement in correlation with glider data during an experiment). Key Points: New altimetry fields allow to characterize mesoscale and coastal processes Spectral content, statistical distribution and EKE are more realistic Comparison with independent data confirms a better description of ocean eddies